The Independent Double-Row (IDR) Bony Bankart Repair Technique - Moroder, Philipp; Paksoy, Alp; Siegert, Paul; Thiele, Kathi; Lacheta, Lucca; Akgün, Doruk (Zeitschrift für Orthopädie und Unfallchirurgie, 2022)
A displaced anterior glenoid rim fracture, the so-called bony Bankart lesion, occurs after a traumatic shoulder dislocation resulting from a high energy trauma and is associated with recurrent shoulder instability. Different surgical techniques have been described in the literature to address this pathology, including open reduction and fixation, as well as arthroscopic transosseous, and single-row or double-row approaches with the use of suture anchors. However, there is currently no gold standard of treatment and the stability of fixation and the healing of the bony fragment are still a concern. The purpose of this report was to introduce an arthroscopic independent double-row (IDR) bony Bankart repair technique for fixation of large glenoid fractures.
Keywords: knöcherne Bankart-Läsion; Doppelreihen-Rekonstruktion; Glenoidkonkavität; Arthroskopie; anatomische Rekonstruktion